Complexation's studies of chenodeoxicholic acid with β-cyclodextrins for preparation of liquid and oral Pharmaceutical forms. Issue 2 (12th March 2012) - Paoletti, D.; D'Elia, B.; Iozzi, D.; Laudisio, C.; Vergati, A.; Tarantino, A.; Corti, I.; D'Arpino, A.; Cesqui, E.; Rossetti, M.G.
Abstract : Background: The cerebrotendinous xanthomatosis is a rare metabolic disease with alterations in hereditary of storage lipids (in Italy, 20 confirmed cases). The basic defect of this disorder is the deficit a liver enzyme (sterol 27alfa-hydroxylase), which catalyses the hydroxylation of a sterol intermediate of the biosynthetic way of bile acids, thus causing the accumulation of cholesterol in most tissues. It's characterised by abundant deposits of cholesterol and cholestanol, mostly in the Achilles' heel, lungs, brain and peripheral nerve myelin. In cerebrotendinous xanthomatosis you have stabilisation or improvement of the neurological and systemic clinical conditions as a result of chronic therapy with chenodeoxicolic acid (CDCA). This drug normalises the main metabolic alteration restoring normal cholestanol levels, with a mechanism of feedback inhibition of 27 alfa –hydroxylase. Purpose: The purpose of this work was the preparation and evaluation of the stability of a liquid formulation oral of CDCA for paediatric use (easy to take and pleasant taste) for the treatment of cerebrotendinous xanthomatosis. Materials and methods: To make the formulation was evaluated the solubility of the drug, the ability to form complexes inclusion with β-cyclodextrin, stability after complexation and the correction of taste and smell. The formation of inclusion complexes between the CDCA and β-cyclodextrins has been carried out both by the method 'Freeze-drying' (in water solution and in water solution with ethanol or methanol) and with the method 'Kneading' (solid state). Obtained in the samples was determined the amount of complex formed with the chromatography LC-MS technique. The stability of the dosage form was tested at room temperature, after storage at 3 ° C and -15 ° C using chromatographic techniques. Results: Chenodeoxicolic acid proved insoluble in water but in the form of β-CD complex has a higher solubility. The complex formed between CDCA and β-CD in 1:5 ratio has been shown to be stable for at least 15 days in water solution (r.t.20°C T0=21.32 mg/ml; T1 after 1 week=20.84 mg/ml; T2 after 2 week=20.72 mg/ml; Fridge 3°C T0=21.08 mg/ml; T1 after 1 week=21.13 mg/ml; T2 after 2 week=20.94 mg/ml; Freezer -15°C T0=20.98;T1 after 1 week=21.08 mg/ml; T2 after 2 week=20.82 mg/ml.) The liquid pharmaceutical form was then created by selecting the mode of complexation and solid state using CDCA and β-CD in 1:5 molar ratios. The preparation was pleasant and palatable. Conclusions: The complexation between CDCA and β-CD allowed to make available a liquid pharmaceutical form of pleasant taste, thus improving a good compliance of paediatric patients.